The Characteristics of al-Qur'an Interpretation in Radical Islamic Sites in Indonesia - Zuhdi, M. Nurdin; Masduki, Mahfudz (KALAM, 2018)
The issue of radicalism has become a serious topic in recent years. The issue of radicalism is not only studied at the national level, but also receives a lot of attention at the global level. Radicalism seems to be considered as a virus endangering humanity. Printed and electronic media are allegedly one of the most effective methods of disseminating the understanding of radicalism. The study examines the characteristics of the interpretation of the verses of the Qur'an in Islamic sites which are indicated to adhere to radicalism. The study also examines the extent of the implications of interpreting the verses of the Qur'an in Islamic sites against the spread of the thoughts of radical Islam in Indonesia. The study is included in the library research category with a media analysis approach. The study focuses on interpreting the verses of the Qur'an embraced in Islamic sites in Indonesia. The research is qualitative in nature. From the analysis carried out on five Islamic sites in Indonesia, four interpretive criteria have been found, namely: interpretation as a mean of ideological legitimacy; loss of contextualization of verses; jihadist interpretations campaign; and the typology of revivalist subjectivists in the typology of interpretation. Thie study concludes that media, both printed and electronic, can influence and change the paradigm of thinking that it can move certain people or groups of people to act or behave in a certain way. Thus, it is obvious that the interpretations of the Qur'an in the Islamic sites indicated as radical can have an influence on the spread of radical Islam.